Shake-Out : Iowa Farm Families in the 1980s - Friedberger, Mark (Book collections on Project MUSE., 2015)
The farm crisis of the 1980s quickly became a media event, with scenes depicted starkly in black and white on color TV. The embattled farmers, accompanied by their advocates, stood holding off bankers and sheriffs wielding foreclosure notices. In this new book, using findings from interviews and participant observation, agricultural historian Mark Friedberger peels away the emotion and rhetoric of the ""save the family farm"" movement to provide a realistic picture of what happened in on important farm state. Shake-out: Iowa Farm Families in the 1980s depicts the farm crisis of the 1980s in al.